POLA PENGGUNAAN RUANG DAN WAKTU RUSA SAMBAR (Rusa unicolor) DI RAGUNAN - Julaili Irni (Mahesa Research Center, 2020)
Daily activities are all activities carried out by animals daily starting from the morning out of the nest until late in the evening and back again to the nest. This study aims to determine the activity pattern of sambar deer (Rusa unicolor). This observation was carried out at the Ragunan zoo which was carried out in 3 stages, namely morning, afternoon and evening. This study observed the patterns of time use and space use observed in sambar deer with 5 age class categories, namely adult males, adult females, young males and young females. The results of the research obtained from the activity of the sambar deer in the morning, namely the allocation of time for daily activities in the morning for each different age class, the allocation of time for feeding, moving, and resting activities during the daytime period for each individual age class of the deer is different and the time allocation for daily activities in the afternoon for each age class is different. Most of the sambar deer in Ragunan prefer to be in the grass below the stands for their activities. Time allocation (time budget) for sambar deer in age class and sex is influenced by the time of activity (morning-afternoon-evening).